Windows 10 inside out - Bott, Ed; Siechert, Carl; Stinson, Craig, 1943- (Inside out (Redmond, Wash.), 2015)
Conquer Windows 10--from the inside out! Dive into Windows 10--and really put your Windows expertise to work. Focusing on the most powerful and innovative features of Windows 10, this supremely organized reference packs hundreds of timesaving solutions, tips, and workarounds. From the new Microsoft Edge browser to the personal assistant Cortana, from security to the enhanced Start menu, discover how the experts tackle essential Windows 10 tasks--and challenge yourself to new levels of mastery. Install, configure, and personalize Windows 10 Transition smoothly from Windows 7 or Windows 8.1 Discover the fast, efficient Microsoft Edge browser Use the Cortana personal assistant to handle reminders and information retrieval Explore cloud services Find, manage, back up, and restore files Use the Windows 10 Mail, Calendar, and People apps Retrieve, organize, and enjoy digital media Harden security and strengthen privacy Add Windows Store apps Fine-tune performance and troubleshoot crashes Share resources and control computers remotely Automate tasks and use advanced system management Run Hyper-V virtual machines For Intermediate and Advanced Users Your role: Experienced intermediate-level to advanced-level Windows user Prerequisites: Basic understanding of Windows procedures, techniques, and navigation.